RBC-Y/MCV as a discriminant function for differentiating carriers of thalassaemia and HbE from iron deficiency - Nadarajan, V.S.; Sthaneshwar, P.; Jayaranee, S. (2010)
P>Individuals with alpha-thalassaemia (ATT), beta-thalassaemia (BTT) and HbE trait (HET) are often initially identified based on haematological parameters. However, the values of these parameters usually overlap with iron deficiency anaemia (IDA) and anaemia of chronic disease (ACD). We evaluated the use of RBC-Y in 156 normal individuals and 332 patients; ATT (n = 37), BTT (n = 61), HET (n = 25), HbH disease (n = 5), ACD (n = 67), IDA (n = 83) and ACD with IDA (n = 54). Diagnostic efficiency was analysed by receiver operating characteristics (ROC). MCH was better compared with RBC-Y in discriminating normal from abnormal with sensitivity and specificity of 94% at a cut-off of 26 pg. The Green and King (G&K) index performed the best in discriminating carriers from IDA and ACD with area under the ROC curve (AUCROC) of 0.81. However, if ACD was excluded, RBC-Y/MCV was a good discriminator for carriers from IDA with AUCROC = 0.845. In general screening of populations with ATT, BTT and HET, we propose that hypochromic individuals be first identified by MCH < 26 pg and carriers distinguished within these hypochromic individuals from IDA by using RBC-Y/MCV. However, if the prevalence of ACD were high within the screening population, G&K index would be a more suitable discriminator.